The Student’s Responses on The Task Given Through Whatsapp Application in Learning English at SMAN 3 Lengayang Pesisir Selatan - Nihalai, Fatricia Golda; Yulmiati, Yulmiati; Ikhsan, M. Khairi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research is motivated by students' responses when given assignments via the Whatsapp application in learning English at SMAN 3 Lengayang Pantai Selatan 2020/2021. This research is qualitative research with a descriptive method which aims to analyze and see perceptions and responses when given assignments via the Whatsapp application. in learning English. To obtain information, researchers conducted interviews, where samples were taken using a purposive sampling method. The total sample in this research was 25 students. The interview was conducted with voice notes via the WhatsApp application. By conducting interviews with 16 questions to students related to student responses. There are types of responses, namely positive and negative responses. The results of this research show that the majority of students have a positive response to the use of the WhatsApp application as a medium in learning because the WhatsApp application is easy to use during the Covid-19 pandemic. Almost no students had a negative response to using this application.